Economic Recovery in North Sumatera Province After the Covid-19 Pandemic, Through MSME Development and Increasing Muslim Friendly Tourism - Tetty Yuliaty; Weni Hawariyuni; Budi Trianto (Journal of International Conference Proceedings, 2021)
The tourism industry and MSMEs can be a driving force for regional economic recovery after the Covid-19 pandemic. Now halal tourism or Muslim friendly tourism, has become an industry that is taken into account in the tourism sector. This study aims to increase Muslim friendly tourism through efforts to develop MSMEs towards economic recovery in the North Sumatra region. So that both businesses can rise and operate better after the covid19 pandemic. By using in-depth interviews and giving questionnaires to MSMEs in North Sumatra, the majority of which are Muslim, as well as potential advantages in the area. It can be seen that all local governments in North Sumatra which have favorite tourist objects/destinations are very supportive of MSMEs in their area, who generally do culinary business. Halal certification assistance from the government, including digital-based training programs and financial assistance, is urgently needed by the community and enables MSMEs to be able to gradually rise after slumping during the COVID-19 pandemic, and slowly realize regional economic recovery. It takes a commitment from all parties to continue to help MSMEs to survive and develop post-covid-19, so that their existence can make an important contribution in supporting halal tourism.